An adaptive self-biased class-e power amplifier - Min, Ke (Nanyang Technological University, 2024)
As the rapid development of 5G system and wireless communication technology, communication systems emphasize more on high-speed and stable information transmission and energy consumption, which directly promotes the update iteration of RF hardware design. As an energy-consuming device and the last stage device of the transmitter, the power amplifier determines the overall performance of the transmitter system. Theoretically, the class E power amplifier can reach 100% efficiency, the energy utilization rate is high, and it has the advantages of simple structure. Therefore, in the environment of highly integrated design and rapid development of mobile devices, Class E power amplifiers with high efficiency have gradually attracted people's attention. Based on 65nm CMOS process, a Class E power amplifier operating in 10GHz is designed. The Class E power amplifier includes a new adaptive self-biased circuit, which raises the average gate voltage of the common-gate transistor through the fast-charging branch. It reduces the on-resistance and the power loss during the charging process, therefore having great efficiency. This structure also maintains a certain voltage swing while increasing the gate voltage of the common-gate transistor. So, it controls the gate-drain voltage and gate-source voltage difference within a safe range during the entire signal cycle, avoiding the risk of breakdown of the gate oxide layer. As verified by Cadence Spectre simulation, under the 1.8V supply voltage, the output power of the Class-E power amplifier is 17.8 dBm, the gain is 12.6 dB, the second-order harmonic suppression is -33.7 dBc, and the power added efficiency is 41.2%,